The effectiveness of a cognitive-behavioral treatment program to reduce the severity of shyness for women with eczema in Sebha (Journal of Human Sciences, 2020)
The aim of the current research is to identify the effectiveness of a cognitive-behavioral treatment program to reduce the severity of shyness in women with Eczema in Sebha, And to find out whether there are statistically significant differences between members of the control and experimental group in the severity of shyness in women with eczema disease, The research included a sample of (20) patients who are being treated by specialized doctors, They were randomly assigned, and the pure results reached the following efficacy of the cognitive-behavioral therapy program in reducing the severity of shyness in women with eczema disease, And the presence of statistically significant differences between the average scores of the experimental group in the pre and post measurements in favor of the post-measurement,and the presence of statistically significant differences between the members of the experimental group and the control group in the post-measurement, in favor of the experimental group.